Bridging Tradition and Innovation: Transforming Islamic Pedagogy for the Twenty-First Century - Faruk Kerem Sentürk; Esraa Al-Sarray; Farouq Ahmad Faleh Alazzam; Ihsan Yilmaz (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
The rapid transformation of contemporary societies driven by globalization, digitalization, artificial intelligence, and technological innovation has created significant challenges and opportunities for educational systems worldwide. This study aims to examine how Islamic pedagogy can bridge tradition and innovation in order to respond effectively to the demands of the twenty-first century. The research employs a qualitative library research approach through a systematic review and thematic analysis of scholarly literature concerning Islamic education, educational innovation, digital pedagogy, human-centered learning, and twenty-first-century competencies. The findings indicate that the foundational concepts of ta‘lim, tarbiyah, and ta’dib remain highly relevant for addressing contemporary educational challenges when integrated with learner-centered pedagogy, digital literacy, critical thinking, creativity, collaboration, and global citizenship education. The study further reveals that successful educational transformation requires holistic alignment among educational philosophy, curriculum design, teacher development, technology integration, and institutional culture. The novelty of this study lies in the development of the Integrative Islamic Pedagogy Framework (IIPF), which synthesizes Islamic educational philosophy, twenty-first-century learning theory, human-centered education, digital pedagogy, and transformative learning into a comprehensive model for educational reform. The study concludes that Islamic pedagogy possesses substantial conceptual resources for fostering ethical, innovative, and socially responsible learners capable of contributing positively to an increasingly interconnected and technologically driven world